Conversational Implicature Types Used in The Movie “Over The Moon” - Ervina Safitri (English Language and Literature, 2023)
Everyone involved in communication knows and accepts communication. Implicature refers to the speaker’s indirect or implicit meaning of utterances. Conversational implicature is something that is implied in the actual use of language. The conversational implicature appears in the movie “Over the Moon”. A movie is a tool to convey various messages to society through motion pictures. The movie consists of conversational implicature aspects of the speakers and the hearers. This research aimed at identifying the types and functions of conversational implicature that was applied by the characters in the movie “Over the Moon”. This research adapted the theory developed by Grice. Grice divided two types of conversational implicature. This research design was descriptive qualitative research. In collecting data, this research applied observational method and note-taking technique. In analysing data, the research applied the pragmatic identity method and competence in equalizing technique. In the presenting research result, this research displayed it narratively and descriptively. Based on the analysis result, the characters applied the types which are Generalized Implicature and Particularized Implicature. The type of particularized implicature was the most occurrence in the characters’ utterances. Therefore, the characters in the movie often have implied meanings.